The Construction of Electric Vehicle Terminology Based on Morphological Processes of Compound, Derivation and Acronym - Qa’is Ghaziyudin,; Wagiati,; Agus Nero Sofyan, (RETORIKA: Jurnal Ilmu Bahasa, 2025)
The development of technology has driven the emergence of electric vehicles as one of the most important innovations in the transportation world that supports environmental sustainability. This study aims to examine the construction of electric vehicle terminology through morphological processes, including compound, derivation, and acronym. The research data was obtained from the electric vehicle User's Manuals available on the official websites of electric vehicle manufacturers. This study uses a qualitative approach, with data in the form of words, phrases, and sentences. The data collection method used was non-participatory observation method, where the researcher observes the construction of electric vehicle terminology through morphological processes of compound, derivation, and acronym, and then records it. Additionally, interviews were conducted with manufacturers, electric vehicle mechanics, linguists, and cultural experts to deepen the understanding of these terminologies. In data analysis, the researcher refers to the theories of McCarty (2002) and Lieber (2009) to classify the morphological processes of word formation based on the identified terminology. This theory was applied to group words, phrases, and sentences containing compounds, derivations, and acronyms. Additionally, Leech's (1981) theory was used to analyze the lexical and grammatical meanings of these terminologies. After the data was collected, a series of analysis stages are carried out, including data reduction, classification, verification, tabulation, interpretation, and conclusion. The results show that there were three types of morphological processes in the formation of electric vehicle terminology: derivation, abbreviation, and compound. Terminology with the derivation process was found in 9 data with the suffix "-ing." Terminology with the abbreviation process was recorded in 25 data, with forms ranging from two to four letters. Meanwhile, terminology with the compound process was found in 14 data, with the most dominant structure being noun + noun. These findings contribute to a better understanding of electric vehicle terminology, which may assist linguists, technical writers, and industry professionals in standardizing terminology use